Sharing family stones In a time of AIDS - Denis, Philippe (Missionalia: Southern African Journal of Mission Studies, 2001)
Children who remember their parents in a positive way when they become iII or when they die are in a better position to cope with the hardships of their condition. The concept of memory boxes are used with positive effect to help AIDS orphans cope with the loss of their parents or siblings. The article reports on a pilot study being conducted jointly by the Oral History Project of the School of Theology, University of Natal and Sinosizo Home Based Care.
Free